Quality versus quantity: assessing individual research performance - Sahel, José-Alain (American Association for the Advancement of Science, 2011)
Evaluating individual research performance is a complex task that ideally examines productivity, scientific impact, and research quality––a task that metrics alone have been unable to achieve. In January 2011, the French Academy of Sciences published a report on current bibliometric (citation metric) methods for evaluating individual researchers, as well as recommendations for the integration of quality assessment. Here, we draw on key issues raised by this report and comment on the suggestions for improving existing research evaluation practices.